CARMENES: M dwarfs and their planets. Issue Volume 11:Issue S320(2015) (9th September 2016) - Quirrenbach, A.; Amado, P.J.; Caballero, J.A.; Mandel, H.; Mundt, R.; Reiners, A.; Ribas, I.; Seifert, W.; Azzaro, M.; Galadí, D.; ,
Abstract: CARMENES (C alarA lto high-R esolution search forM dwarfs withE xo-earths withN ear-infrared and opticalE chelleS pectrographs) is a new instrument currently undergoing commissioning at the 3.5 m telescope of the Calar Alto Observatory. It has been constructed by a consortium of eleven Spanish and German institutions. The scientific goal of the project is a 600-night radial-velocity survey targeting 300 M dwarfs with sufficient precision to detect terrestrial planets in their habitable zones. The CARMENES instrument consists of two separate échelle spectrographs covering the wavelength range from 0.55 to 1.7 μm at a spectral resolution of R = 82, 000, fed by fibers from the Cassegrain focus of the telescope. Both spectrographs are housed in a temperature-stabilized environment in vacuum tanks, to enable a long-term radial velocity precision of 1 m s −1 . The wavelength calibration will be done with Th-Ne and U-Ne emission line lamps, and with Fabry-Pérot etalons.